Death by sheer torture - Barnard, Robert
Inspector Perry Trethowan reads in the obituaries that his estranged father has died under peculiar he was fooling around with a form of self-torture called strappado. At the request of his supervisor, Peter returns to his ancestral home to determine if any of his cousins or siblings might have helped the old man to his bizarre end.